(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Effect of Artemisia plant Extract (APE) on the copper corrosion as a corrosion inhibitor in an aerated acidic solution of in 2M H3PO4 containing 3.10-1 M NaCl has been investigated using gravimetric and electrochemical techniques. A significant decrease in the corrosion rate of copper was observed in the presence of the Artemisia plant extract. The potentiodynamic polarization data indicated that the inhibitor was of mixed type. Impedance measurements showed that the charge transfer resistance increased and double layer capacitance decreased with increase in the inhibitor’s concentration. Also, some thermodynamic data for the activation are calculated and discussed. The results obtained from potentiodynamic polarization, impedance measurements and gravimetric method are in good agreement.